Disruption of Elementary School Students' Learning Concentration in the Digital Era: An Analysis of Determinant Factors and Islamic Educational Strategies - Nur Manna; Gusmirawati Gusmirawati; Martin Kustati; Rezki Amelia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of digital technology has provided students with easier access to information; however, it has also created various challenges in the learning process, one of which is the disruption of learning concentration. This study aims to analyze the forms of learning concentration disruption among elementary school students, identify the factors influencing it, and formulate reinforcement strategies based on Islamic Education to address the issue. The research employed a qualitative approach with a field research design conducted at SD Negeri Kampung Tampang. The research participants consisted of the principal, Islamic Education teachers, homeroom teachers, parents, and students. Data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings revealed that disruptions in students’ learning concentration were characterized by a lack of focus during lessons, a tendency to chat while teachers were explaining, playing during learning activities, and a lack of responsibility in completing school assignments. Factors contributing to this condition included uncontrolled gadget use, insufficient parental supervision, weak communication between parents and the school, peer influence, and low learning discipline among students. Islamic Education-based strategies that can be implemented include strengthening “adab al-muta'allim” (student ethics), cultivating the value of “muraqabah” (self-awareness of God's supervision), applying “ta'dib” through teachers’ role modeling, and reinforcing partnerships between families and schools. These strategies are expected to enhance students’ learning concentration, discipline, and sense of responsibility in facing the challenges of the digital era.